Extracellular vesicles rejuvenate the microenvironmental modulating function of recipient tissue-specific mesenchymal stem cells in osteopenia treatment - Sonoda, Soichiro; Yamaza, Takayoshi (Frontiers in Endocrinology, 2023)
Systemic transplantation of mesenchymal stem cells (MSCs), such as bone marrow MSCs (BMMSCs) and stem cells from human exfoliated deciduous teeth (SHED), is considered a prominent treatment for osteopenia. However, the mechanism of action of the transplanted MSCs has been poorly elucidated. In the recipient target tissue, including bone and bone marrow, only a few donor MSCs can be detected, suggesting that the direct contribution of donor MSCs may not be expected for osteopenia treatment. Meanwhile, secretomes, especially contents within extracellular vesicles (EVs) released from donor MSCs (MSC-EVs), play key roles in the treatment of several diseases. In this context, administrated donor MSC-EVs may affect bone-forming function of recipient cells. In this review, we discuss how MSC-EVs contribute to bone recovery recipient tissue in osteopenia. We also summarize a novel mechanism of action of systemic administration of SHED-derived EVs (SHED-EVs) in osteopenia. We found that reduced telomerase activity in recipient BMMSCs caused the deficiency of microenvironmental modulating function, including bone and bone marrow-like niche formation and immunomodulation in estrogen-deficient osteopenia model mice. Systemic administration of SHED-EVs could exert therapeutic effects on bone reduction via recovering the telomerase activity, leading to the rejuvenation of the microenvironmental modulating function in recipient BMMSCs, as seen in systemic transplantation of SHED. RNase-preconditioned donor SHED-EVs diminished the therapeutic benefits of administrated SHED-EVs in the recipient osteopenia model mice. These facts suggest that MSC-EV therapy targets the recipient BMMSCs to rejuvenate the microenvironmental modulating function via telomerase activity, recovering bone density. We then introduce future challenges to develop the reproducible MSC-EV therapy in osteopenia.